The quest for expansive intellectual property rights and the failure to disclose known relevant prior art. (19th June 2014) - Steensma, H. Kevin; Chari, Mukund; Heidl, Ralph
<x xml:space="preserve">Abstract</x> Expansive patent portfolios may be used by firms to fence off technological space for commercialization, impede the commercialization efforts of competitors, and enhance bargaining power in cross‐licensing negotiations. Low quality patents with claims that overlap those of other patents contribute to these portfolios and patent strategies. By failing to disclose known relevant prior art during the patenting process, inventors and their firms may be granted low quality patents with intellectual property claims which would not otherwise have been granted. We find that the failure of inventors to disclose known relevant prior art increases as they gain experience with the patenting process. Such failure is also greater among inventors employed by relatively small, poorly performing firms that rely on outsourced legal counsel during the application process. Copyright © 2014 John Wiley & Sons, Ltd.